Tendências hidrológicas anuais e sazonais na bacia do Rio Paraibuna, Parque Estadual da Serra do Mar (SP) - Vilanova, Mateus Ricardo Nogueira (Universidade Federal de Uberlândia, Instituto de Geografia, Programa de Pós-Graduação em Geografia, 2014)
This article assesses the existence of monotonic trends in streamflow and rainfall series, in the stretch of Paraibuna River Watershed located in the region of Santa Virgínia and Cunha Centers, Serra do Mar Range State Park (SP). The Mann-Kendall test was applied to annual and seasonal series of the mentioned variables, in several intervals during the period of 1967 to 2011. Statistically significant negative trends were detected only in the long-term (from 1967) rainfall series, both annual and seasonal, from station 2344009, located in the region of Cunha. No significant trends were detected in the series of stations 2345067 (rainfall) and 58060000 (streamflow), located in Santa Virginia Center.

O presente trabalho avalia a existência de tendências monotônicas em séries anuais e sazonais de vazão e chuva, no trecho da Bacia do Rio Paraibuna localizado entre os Núcleos Cunha e Santa Virgínia, Parque Estadual da Serra do Mar (SP). O teste de Mann-Kendall foi aplicado a séries destas variáveis, em diversos intervalos no período de 1967 a 2011. Tendências negativas estatisticamente significativas foram detectadas nas séries de chuva de longo prazo (a partir de 1967), anuais e sazonais, da estação 2344009, localizada na região de Cunha. Não foram detectadas tendências significativas nas séries das estações 2345067 (pluviométrica) e 58060000 (fluviométrica), localizadas no Núcleo Santa Virgínia.
Annual and seasonal hydrological trends in Paraibuna river watershed, Serra do Mar State Park, São Paulo, Brazil
Keywords: Hydrological variability; Climate change; Serra do Mar State Park; Variabilidade hidrológica; Mudança climática, Núcleo Santa Virgínia; Núcleo Cunha